The Voices of the Regional Museum of São João del Rei (Cadernos de Sociomuseologia, 2021)
This thesis is an exercise of listening, reflection and collective action. We do the register of the institutional history through primary and secondary sources, in which the modern oral history brought the voices of employees as protagonist of this historical document. As a result, several points of views were unveiled and brought diversity of experiences about political interferences, of different managements, interventions in personal life, family life, how employees viewed this museum and other topics. Besides the modern oral history, several endogenous and exogenous educational actions were accomplished, having as main focus to sensitize the internal public. All of this processes were accomplished through liberating education and an integrative museology. The experiences passed through to everyone involved in these museum processes, we brought the perspective of Sociomuseology to a federal and traditional museum. The submerged history is brought to this academic work through the methodology of oral history, the education actions were developed in many different ways and were monitored, registered and analyzed through action-research and the generative management was implemented. An institucional history document was produced with the voices of the internal public as the bond between the past time, present and desire for the future. The museum was transformed into a great liberating educational action in which the employees became agents of the development of the institution and the community. The whole process was based on action-reflection-action collectively, brought maturity to the team and they started to feel part of the museum. The utilization of the modern oral history, raise the self-esteem, improve the quality of internal and external life, became involved in all actions and with that, the museum practices were enchanted. Hearing these voices, processing, changing looks through the experience of the other, the constant dialogic actions increased the involvement, and the museum experienced an integrative organic museology, expanded its performance and capillarity resulting in a greater insertion of the community. Keywords: Museu Regional de São João del Rei, Sociomuseology, Oral history, Museum management, Museum audiences, Museum education.